Structure, Mechanical, and Lytic Stability of Fibrin and Plasma Coagulum Generated by Staphylocoagulase From Staphylococcus aureus - Farkas, Ádám Z.; Farkas, Veronika J.; Szabó, László; Wacha, András; Bóta, Attila; Csehi, Lóránt; Kolev, Krasimir; Thelwell, Craig (Frontiers in Immunology, 2019)
Staphylococcus aureus causes localized infections or invasive diseases (abscesses or endocarditis). One of its virulence factors is staphylocoagulase (SCG), which binds prothrombin to form a complex with thrombin-like proteolytic activity and leads to uncontrolled fibrin generation at sites of bacterial inoculation. The aim of this study was to characterize the formation, structure, mechanical properties and lysis of SCG-generated clots. Recombinant SCG was expressed in Escherichia coli, purified and the amidolytic activity of its complexes with human prothrombin (SCG-PT) and thrombin (SCG-T) was determined using human thrombin as a reference. Fibrin clots were prepared from purified fibrinogen and human plasma using thrombin, SCG-PT or SCG-T as a coagulase. The kinetics of clot formation and lysis by tissue-type plasminogen activator (tPA) were monitored with turbidimetric assays. Fibrin ultrastructure was examined with scanning electron microscopy and small-angle X-ray scattering (SAXS). Fibrin clot porosity was characterized with fluid permeation assays, whereas the viscoelastic properties and mechanical stability were evaluated with oscillation rheometry. Compared to thrombin, the amidolytic and clotting activity of SCG-PT was 1.6 to 2.5-fold lower on a molar basis. SCG-T had equivalent amidolytic, but reduced clotting activity both on pure fibrinogen (1.6-fold), and in plasma (1.3-fold). The SCG-PT and SCG-T generated fibrin with thicker fibers (10 to 60 % increase in median diameter) than thrombin due to increased number of fibrin protofibrils per fiber cross-section. According to the fluid permeability of the clots SCG-PT and SCG-T promoted the formation of more porous structures. The shear stress resistance in the pure fibrin and plasma clots generated by SCG-PT was significantly lower than in the thrombin clots (243.8±22.0 Pa shear stress was sufficient for disassembly of SCG-PT fibrin versus 937.3±65.6 Pa in thrombin clots). The tPA-mediated lysis of both pure fibrin and plasma clots produced by SCG-PT or SCG-T was accelerated compared to thrombin, resulting in up to a 2.1-fold increase in tPA potency. Our results indicate that SCG generates a thrombus scaffold with a structure characterized by impaired mechanical stability and increased lytic susceptibility. This proneness to clot disintegration could have implications in the septic embolism from endocardial bacterial vegetation.